2017
DOI: 10.1163/22134808-00002569
|View full text |Cite
|
Sign up to set email alerts
|

Sounds Are Perceived as Louder When Accompanied by Visual Movement

Abstract: In this study, we present three experiments investigating the influence of visual movement on auditory judgments.In Experiments 1 and 2, two bursts of noise were presented and participants were required to judge which was louder using a forced-choice task. One of the two bursts was accompanied by a moving disc. The other burst either was accompanied by no visual stimulus (Experiment 1) or by a static disc (Experiment 2). When the two sounds were of identical intensity participants judged the sound accompanied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…Whatever the underlying mechanisms, our results reveal that we cannot generalize the influence of reward to all dimensions of visual perception. This result echoes recent findings that visual motion does not affect all dimensions of auditory perception (Maniglia, Ward, & Grassi, 2017). Evidencing the limits of contextual influences on perception represents an important step toward understanding the origins and functions of such phenomenon (Firestone & Scholl, 2016).…”
Section: Discussionsupporting
confidence: 87%
“…Whatever the underlying mechanisms, our results reveal that we cannot generalize the influence of reward to all dimensions of visual perception. This result echoes recent findings that visual motion does not affect all dimensions of auditory perception (Maniglia, Ward, & Grassi, 2017). Evidencing the limits of contextual influences on perception represents an important step toward understanding the origins and functions of such phenomenon (Firestone & Scholl, 2016).…”
Section: Discussionsupporting
confidence: 87%
“…Store’s sensory intensity can be varied by the magnitude of one sensory cue or the appearance of multiple sensory cues together. For instance, in Maniglia et al (2017) study, participants were presented with two bursts of identical noise, in which a moving disc accompanied one condition while the other was not. The authors revealed that participants perceived a louder noise in the moving disc condition than the other (Maniglia et al , 2017).…”
Section: Review Of Relevant Literaturementioning
confidence: 99%
“…For instance, in Maniglia et al (2017) study, participants were presented with two bursts of identical noise, in which a moving disc accompanied one condition while the other was not. The authors revealed that participants perceived a louder noise in the moving disc condition than the other (Maniglia et al , 2017). Prior sensory marketing studies indicate the importance of sensory intensity.…”
Section: Review Of Relevant Literaturementioning
confidence: 99%
“…Detection based approaches confine themselves to find out whether a subject has heard the tone or not by incorporating a simple YES-NO approach, whereas discrimination-based techniques probe further to differentiate a given pair of tones as inputs. These paradigms are developed using adaptive techniques wherein the sound is varied based on the previous response of the individual, while the non-adaptive techniques do not use any such feedback to vary the sound and the same is achieved by a predefined protocol such as step, ramp or staircase approaches [6].…”
Section: Absolute Thresholdmentioning
confidence: 99%